HIV-1 transmission and acute HIV-1 infection. - Hansasuta, P; Rowland-Jones, S (2001)
An understanding of the central events in the transmission of HIV-1 infection is critical to the development of effective strategies to prevent infection. Although the main routes of transmission have been known for some time, surprisingly little is known about the factors that influence the likelihood of transmitting or acquiring HIV-1 infection. Once infection has taken place, the series of virological and immunopathological events that constitute primary HIV-1 infection are thought to be closely linked with the subsequent clinical course of the infected person. Recent studies have provided some support for the notion that intervention with aggressive anti-retroviral drug therapy at this stage has the potential to prevent some of the damage to the immune system that will otherwise develop in the vast majority of infected people.